During analysis, language rules are applied to the parsed text. This involves comparing each word against a dictionary or a set of predefined language rules to determine if it is spelled correctly. - Slamet Riyani; Anto Seno (International Journal of Educational Evaluation and Policy Analysis, 2024)
This journal discusses the secession of Mas Marco Kartodikromo, a famous Indonesian writer, and his work which describes the journey of Indonesian literature. This separation refers to how Mas Marco Kartodikromo succeeded in creating his identity in the world of Indonesian literature through his unique and profound work. This journal also explores the relationship between the writer's personal life and the literary stories he produced